Four-year follow-up on a Zephyr Surgical Implants 375 artificial urinary sphincter for male urinary incontinence from one urological centre in Poland - Ostrowski, Ireneusz (Cent European J Urol, 2018)
INTRODUCTION: The treatment of choice for patients who have iatrogenic urinary incontinence is the implantation of an artificial urinary sphincter. We performed a prospective study on the outcomes of men undergoing artificial urinary sphincter (AUS) implantation (ZSI 375; Zephyr Surgical Implants, Geneva, Switzerland). MATERIAL AND METHODS: Patients with moderate-to-severe stress incontinence urinary were included. The ZSI 375 device is a one-piece device with a cuff and a pump unit. Patients underwent a perineal incision for cuff insertion and an inguinal incision for the pump unit to be placed in the scrotum. Complications and number of pads used to manage incontinence were recorded. Perioperative complications were categorized according to the Clavien-Dindo classification. Pain connected with implantation of AUS was assessed with the visual analogue scale (VAS). RESULTS: Between July 2013 and June 2017, 50 patients underwent ZSI 375 device insertion in the Department of Urology and Urological Oncology in Puławy, Poland. The follow-up stopped at the end of September 2017. The median (range) follow-up was 21.04 (1–50) months. No patient experienced bladder hyperactivity. Complications leading to a revision or permanent device removal arose in 12 patients (erosion = 9, infection = 0, mechanical failure = 3). Social continence (0 or 1 pad/day) was achieved in 29/50 patients (58%). An improvement (50% less pads/day) was achieved in 15/50 patients (30%). A failure was seen in 6/50 patients (12%). Perioperatively, all patients were classified as grade I in the Clavien-Dindo classification. Mean value of pain intensity in VAS was 0.82. CONCLUSIONS: The ZSI 375 device is safe, effective and the follow-up period was long enough to identify all potential complications.